Poor hamstrings-to-quadriceps torque ratios in male soccer players: weak hamstrings, strong quadriceps, or both? - Fritsch, C. G.; Dornelles, M. P.; Oliveira, G. S.; Baroni, B. M. (Sports Biomechanics, 2023)
This study aimed to evaluate the influence of hamstrings and quadriceps strength on the hamstrings-to-quadriceps conventional (H:Qcon) and functional (H:Qfun) ratios in male soccer players. Quadriceps concentric peak torque (PT) and hamstrings concentric and eccentric PT were assessed with isokinetic dynamometry at 60°/s in 101 players (202 legs). The cut-points of 0.50, 0.55 and 0.60 were used to assess muscle imbalance through the H:Qcon ratio, while 0.80, 0.85 and 0.90 were used for H:Qfun ratio. Legs with lower H:Qcon ratio had decreased hamstrings concentric PT (p < 0.01; moderate and large effect sizes) and increased quadriceps concentric PT (p < 0.01; moderate effect sizes) in all cut-points. Legs with lower H:Qfun ratio had decreased hamstrings eccentric PT (p < 0.01; large effect sizes) for all cut-points, and controversial results for quadriceps concentric PT (p < 0.01 only for 0.80 cut-point; small effect sizes). H:Qcon ratio presented only weak correlations with quadriceps (r = -0.37) and hamstrings (r = 0.45) concentric PT, while H:Qfun ratio had a negligible correlation with quadriceps concentric PT (r = -0.30) and a moderate correlation with hamstrings eccentric PT (r = 0.66). In conclusion, our findings support that hamstrings strength deficit is the key factor for low H:Q ratios in male soccer players, especially those with poor H:Qfun ratio.